2015
DOI: 10.9775/kvfd.2015.13479
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen Uygulamasının Süt İneklerindeki Erken Laktasyon Döneminde Lipit Mobilizasyon, Ketogenez ve Metabolik Adaptasyon Üzerine Etkisi

Abstract: Changes in metabolic functions in transition dairy cows represent a result of negative energy balance. This leads to increased lipid mobilization and ketogenesis, followed by increased concentrations of non-esterified fatty acids (NEFA) and beta-hydroxybutyrate (BHB). Hence, high lipid mobilization and ketogenesis modulate inflammation response and vice versa. The aim of this study was to investigate correlations between ketoprofen administration, high lipid mobilization, ketogenesis and characteristics of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ketoprofen (KTP) or 2-(phenyl3-benzoyl) propionic acid is a nonsteroidal anti-inflammatory drug (NSAID) that is commonly used in a wide range of indications, both in human and veterinary medicine as an anti-inflammatory, antipyretic and analgesic medicine (Lees et al 2004, Pardon et al 2012. Our previous study has confirmed that ketoprofen applied in the first days after calving reduces the metabolic adaptation dependence on the intensity of lipid mobilization and ketogenesis during early lactation (Kovacevic et al 2016), but we have not examined milk production and its association with metabolic and inflammatory parameters.…”
Section: Introductionmentioning
confidence: 91%
“…Ketoprofen (KTP) or 2-(phenyl3-benzoyl) propionic acid is a nonsteroidal anti-inflammatory drug (NSAID) that is commonly used in a wide range of indications, both in human and veterinary medicine as an anti-inflammatory, antipyretic and analgesic medicine (Lees et al 2004, Pardon et al 2012. Our previous study has confirmed that ketoprofen applied in the first days after calving reduces the metabolic adaptation dependence on the intensity of lipid mobilization and ketogenesis during early lactation (Kovacevic et al 2016), but we have not examined milk production and its association with metabolic and inflammatory parameters.…”
Section: Introductionmentioning
confidence: 91%
“…The use of various NSAIDs leads to a decrease in lipid mobilization and ketogenesis due to a reduction in the concentration of proinflammatory cytokines (Kushibiki et al 2001, Bertoni et al 2004, Medzhitov 2008. According to the results of our previous research, ketoprofen treatment immediately after calving reduces metabolic adaptation dependence on the intensity of lipid mobilization and ketogenesis during early lactation (Kovacevic et al 2016a) and hematological parameters dependence on the intensity of these two processes (Kovacevic et al 2016b).…”
Section: Introductionmentioning
confidence: 94%